Besnoitia besnoiti–driven endothelial host cell cycle alteration - Velásquez, Zahady D. (Parasitol Res, 2020)
Besnoitia besnoiti is an important obligate intracellular parasite of cattle which primarily infects host endothelial cells of blood vessels during the acute phase of infection. Similar to the closely related parasite Toxoplasma gondii, B. besnoiti has fast proliferating properties leading to rapid host cell lysis within 24–30 h p.i. in vitro. Some apicomplexan parasites were demonstrated to modulate the host cellular cell cycle to successfully perform their intracellular development. As such, we recently demonstrated that T. gondii tachyzoites induce G2/M arrest accompanied by chromosome missegregation, cell spindle alteration, formation of supernumerary centrosomes, and cytokinesis impairment when infecting primary bovine umbilical vein endothelial cells (BUVEC). Here, we follow a comparative approach by using the same host endothelial cell system for B. besnoiti infections. The current data showed that—in terms of host cell cycle modulation—infections of BUVEC by B. besnoiti tachyzoites indeed differ significantly from those by T. gondii. As such, cyclin expression patterns demonstrated a significant upregulation of cyclin E1 in B. besnoiti–infected BUVEC, thereby indicating parasite-driven host cell stasis at G1-to-S phase transition. In line, the mitotic phase of host cell cycle was not influenced since alterations of chromosome segregation, mitotic spindle formation, and cytokinesis were not observed. In contrast to respective T. gondii–related data, we furthermore found a significant upregulation of histone H3 (S10) phosphorylation in B. besnoiti–infected BUVEC, thereby indicating enhanced chromosome condensation to occur in these cells. In line to altered G1/S-transition, we here additionally showed that subcellular abundance of proliferating cell nuclear antigen (PCNA), a marker for G1 and S phase sub-stages, was affected by B. besnoiti since infected cells showed increased nuclear PCNA levels when compared with that of control cells.